Flame-retardant PNIPAAm/sodium alginate/polyvinyl alcohol hydrogels used for fire-fighting application: Preparation and characteristic evaluations. (1st March 2021) - Yu, Zhicai; Liu, Jinru; He, Hualing; Ma, Shengnan; Yao, Jinyin
Graphical abstract: Highlights: A flame retardant hydrogel composed of PNIPAAm, SA and PVA was prepared. The hydrogel exhibited excellent swelling-deswelling behavior and thermal stability. Hydrogel-fabric laminates were nearly undamaged when exposed to fire for 12 s. Fire-retardant mechanism is due to release energy was absorbed as water heat up. Abstract: A novel fire-preventing triple-network (TN) hydrogel was prepared and laminated on cotton fabric to improve fire-resistant performance of cellulose fabric. The TN hydrogel composed of Poly (N-isopropylacrylamide) (PNIPAAm)/sodium alginate (SA)/ Poly (vinyl alcohol) (PVA) exhibited excellent swelling ratio, swelling-deswelling behavior and antibacterial property. Results indicated that introduction of SA could improve water retention capabilities of TN hydrogels. Thermogravimetric experiments showed that the thermal stability of hydrogels was best at a SA: PVA ratio of 2:1. Furthermore, the obtained hydrogel-cotton fabric laminates displayed efficient flame retardancy. Compared to original fabric, hydrogel-fabric laminates were nearly undamaged when exposed to fire for 12 s. This result is attributed to energy absorption as water is heated and evaporates in the hydrogel. The present work provides a new concept to prepare fire-resistant polymer fabric, which may be used in fire-protective clothing to protect the skin from burn injuries.